Evaluation of Pile Lateral Capacity in Clay Applying Evolutionary Approach - Alkroosh, Iyad; Nikraz, Hamid (The Geomate International Society, 2013)
This paper presents the development of a new model to predict the lateral capacity of piles inserted into clayey soils and subjected to lateral loads. Gene Expression Programming (GEP) has been utilized for this purpose. The data used for development of the GEP model is collected from the literature and comprise 38 data points. The data are divided into two subsets: Training set for model calibration and independent validation set for model verification. Predictions from the GEP model are compared with the results of experimental data. The model has achieved a coefficient of correlation, r, of 0.95 for training and validation sets and average prediction ratio (APR) of 0.97 and 1.04 for training and validation sets respectively. The results indicate that the GEP model performs very well and able to predict the pile lateral capacity accurately.